Effects of Sodium Sulfate Attack on Concrete Incorporated with Drying-Wetting Cycles - Fang Liu; Zhanping You; Rui Xiong; Xu Yang (Advances in Civil Engineering)
It has been widely observed that sulfate attack can damage the durability of concrete. This research investigated the mass loss and damage degree of concrete under sodium sulfate attack incorporated with drying-wetting cycles. The impact factors, including water-binder ratio, solution concentration of sodium sulfate, fly ash content, curing time, and drying-wetting cycle system, were observed to influence the sodium sulfate attack by the mass loss rate and damage degree at regular time intervals. Also, the hydrates of sulfate-attacked samples were analyzed using X-ray diffraction. Results indicated that a high water-binder and high-concentration sodium sulfate solution could accelerate the transportation of sulfate ion inside the concrete and the deterioration degree of concrete. Appropriate fly ash and longer curing time can effectively improve the internal pore structure of concrete to reduce the sulfate corrosion damage. The sulfate ion erosion and deterioration degree of the concrete are synchronously intensified along with the increase of the baking-immersing time ratio. The trend of the predicted life for concrete is basically consistent with the damage evolution result, indicating the feasibility of the Weibull distribution model to predict the service life of concrete under sodium sulfate attack incorporated with drying-wetting cycles.